Pilot Trial of Midstream Urine Collection Device Versus Transurethral Catheter in Women With Lower Urinary Tract Symptoms: Practicality of Use in a Clinical Setting, Patient Preferences, and Comparison of Laboratory Findings. Issue 6 (June 2021) - High, Rachel; Zhang, Yu; Virani, Shohaib; Eggleston, Kimberly; Kuehl, Thomas J.; Bird, Erin T.; Danford, Jill M.
Abstract : Objectives: This study aimed to evaluate successful use of a midstream urine collection device in women with lower urinary tract symptoms and to assess specimen contamination. Methods: Nonpregnant women 18 years or older without use of antibiotics in the last 4 weeks were recruited. After using the midstream urine collection device to obtain a specimen in a private restroom, a paired specimen was obtained by transurethral catheterization. Patients completed preference questionnaires. Culture organisms and microscopic urinalysis of paired specimens (device vs catheterized) were compared using the McNemar χ 2 test. Bivariate analysis was performed. Results: Successful use was demonstrated in 54 (77%) of 70. Reasons for failure included inadequate specimen volume and improper device use. Older median age (50 vs 72 years, P = 0.0003) and history of diabetes (7% vs 27%, P = 0.037) were associated with failed use. Organisms were discordant in 21 (41%) of 51 paired urine culture specimens. The device detected 7 (88%) of 8 uropathogens. There were no detectable differences in microscopic urinalysis. Conclusions: The midstream urine collection device could increase comfort, and many patients prefer it to transurethral catheterization. With proper patient selection and instructions for use, this device could increase satisfaction. Further studies are needed to assess contamination rates with this device.